Educational Effects of Stop Smoking in Adolescents in the Covid-19 Pandemic - Heni Nurhaeni; Supriatin Supriatin; Mira Rosmiatin (International Journal of Nursing Information, 2022)
Smoking not only has an impact on yourself but also has an impact on the people around you. Cigarettes have always been a unique phenomenon worldwide. Stop smoking, but cigarette excise is one of the country's significant foreign exchange. The dangers of smoking can interfere with/inhibit the function of the brain, mouth, throat, lungs, stomach, bones, skin, and reproductive organs. This study aimed to determine the effect of the Covid-19 pandemic on adolescent smoking behavior by providing education through counseling to stop smoking. This study uses a survey methodology and quantitative literature studies. The research locations are in two junior high schools in Jakarta. The sample is 60, with details of each junior high school amounting to 30. The results show that the characteristics of adolescent smokers aged 12 to a maximum of 16 years, there are sources of exposure to smoking most commonly found in their family members. There was no effect found on the characteristics of young smokers on the status of the covid-19 pandemic for young smokers, including stop smoking information sources. This research contributes to providing information about activities of stopping smoking during the Covid-19 pandemic.